A second species of Psyllototus (Coleoptera: Chrysomelidae: Galerucinae) - Bukejs, Andris; Nadein, Konstantin (Zootaxa, 2013)
Psyllototus doeberli sp. nov., a second species of the paleoendemic genus is described. This is the first named species of Alticini from the Upper Eocene Baltic amber of Yantarny, Kaliningrad region, Russia. A checklist of known Alticini from fossil resins is provided.